Organizational work climate and perceived 'procedural fairness' of human resource practice - Bose, Sudeepa; Agarwal, Manisha (2005)
The study examined the relationship between the organization's work climate and members' perception of procedural 'fairness' in public and private sector Indian organizations. The participants included managerial and supervisory personnel from two private sector and two public section manufacturing organizations in North India. The results revealed that an organizational climate that ensures system-support for innovation, interpersonal trust between the superior and the subordinate and participation in decision-making and member welfare was positively related with perceptions of procedural fairness among organizational members. Findings indicate that organizations, which would like to ensure member loyalty in the context of a changing environment, should focus primarily on creating a positive work climate that can facilitate perceptions of procedural 'fairness' in their human resource practices. -Reproduced.
Keywords: Work environment; Organizations; Human resources development